Preventive Effect of Liupao Tea Polyphenols on HCl/Ethanol-Induced Gastric Injury in Mice - Kai Zhu; Peng Peng; Ning Wu; Xianrong Zhou; Jianfei Mu; Xin Zhao (Journal of Food Quality)
Liupao tea is a traditional Chinese tea drink. The preventive effect of crude polyphenols in Liupao tea on HCl/ethanol-induced gastric injury was investigated in this study. After a model of gastric injury in mice was established, mouse serum and tissues were analyzed by biochemical and molecular biological methods. The results showed that Liupao tea polyphenols (LTPs) could effectively reduce the area of gastric mucosal lesions, decrease the volume of gastric juice, and increase the pH of gastric juice in mice with gastric injury. Observations of the pathology revealed that LTPs could alleviate cell necrosis and gastric mucosal injury in mice with gastric injury. The SOD activity and GSH level were decreased in mice after gastric injury, while the level of MDA was increased. LTPs could inhibit the changes caused by gastric injury and make the SOD activity, GSH, and MDA levels close to the normal levels. In addition, LTPs could upregulate the mRNA expression of Cu/Zn-SOD, Mn-SOD, CAT, nNOS, and eNOS and downregulate the expression of iNOS in the gastric tissue of mice with gastric injury. Therefore, LTPs can effectively prevent HCl/ethanol-induced gastric injury. HPLC analysis showed that LTP contains six bioactive substances of gallic acid, catechin, caffeine, epicatechin, epigallocatechin gallate, and epicatechin gallate, so the effect of LTP might mainly come from these six components. The effect of a high concentration of LTP is similar to that of ranitidine. LTPs represent a kind of active substance with a protective effect on gastric tissue.